Discourse of Public Sexual Harassment: Identity Construction in Sexually Harassed Teenage Girls’ Narratives of Personal Experiences - Abdelhadi, Amina; Abdelhay, Bakhta (المركز الجامعي بلحاج بوشعيب عين تموشنت - مخبر الخطاب التواصلي, 2018)
This paper reports on an ongoing research project in public sites in North West of Algeria where sexually harassed teenage girls are every day treated like a piece of public property. Its emphasis is on their narratives of personal experiences examining how linguistic resources are used to index their distinct identities. This paper expands this view by focusing up on cases where these survivors are blamed and forced to accept occupied identities and show no sign of agency when telling those narrative discourses. Many of the stories told by them reveal a picture of extensive abuse that affects their lives, but is systematically underreported to the authorities. This underscores the several ways in which their perceptions of public sexual harassment is both discursively gendered in the name of the so-called honourable cultures and the social gender norms, while in turn these cultural and sexist beliefs serve to consider their bodies as objects that need self- surveillance within such panoptic patriarchal contexts and therefore legitimize the violation of their rights.
Keywords: الخطاب النقدي -- العنف الجنسي -- النوع الأجتماعي